2014
DOI: 10.1016/j.compedu.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a meta-tutor for constructing models of dynamic systems

Abstract: Abstract. While modeling dynamic systems in an efficient manner is an important skill to acquire for a scientist, it is a difficult skill to acquire. A simple step-based tutoring system, called AMT, was designed to help students learn how to construct models of dynamic systems using deep modeling practices. In order to increase the frequency of deep modeling and reduce the amount of guessing/gaming, a meta-tutor coaching students to follow a deep modeling strategy was added to the original modeling tool. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Drawing on previous work on model progression (Mulder et al, 2011), it was deemed more effective to provide students with a global outline of the entire model instead of with a fully specified part of the larger model. This top-down approach also mirrors what experts and successful learners do in the model formulation stage: they first determine the overall structure of the model before going into the model details (Wu et al, 2013;Zhang et al, 2006). Another, more practical reason for providing these model components was that participants in our previous studies often struggled with the concept of inflow and outflow, and found it difficult to determine to which variables these relation arrows should be attached.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…Drawing on previous work on model progression (Mulder et al, 2011), it was deemed more effective to provide students with a global outline of the entire model instead of with a fully specified part of the larger model. This top-down approach also mirrors what experts and successful learners do in the model formulation stage: they first determine the overall structure of the model before going into the model details (Wu et al, 2013;Zhang et al, 2006). Another, more practical reason for providing these model components was that participants in our previous studies often struggled with the concept of inflow and outflow, and found it difficult to determine to which variables these relation arrows should be attached.…”
Section: Methodsmentioning
confidence: 86%
“…For instance, Löhner, van Joolingen, and Savelsbergh () showed that students benefit from a graphical modelling language that makes use of the traditional “stock and flow” language (Forrester, ) compared to a text‐based language. Students’ model formulation also benefits from constraining scaffolding approaches that organize the task according to a simple‐to‐complex sequence in order to prevent them from getting overwhelmed by the complexity of the task (e.g., Mulder et al, , ; Zhang et al, ). The success of such incremental approaches might derive from the fact that students can focus on the model structure outline first before considering the models’ behavior.…”
Section: Supporting Learning By Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Paiva et al (2015) present the project design features, its development and implementation, evaluation of the tools used and results of studies with the students involved in the project. This paper describes the design, development, implementation and evaluation of an intelligent online tutoring system (TS) (Chrysafiadi and Virvou 2013;Kularbphettong et al 2015;Zhang et al 2014) designed to teach or to remind math concepts essential for the integration of students of engineering, economics, management, among others, in mathematics higher education. The TS, which we developed in MITO platform, consists of small self-paced modularized units of educational contents including tutorial videos, notes and formative eassessments with personalized feedback.…”
Section: Introductionmentioning
confidence: 99%
“…If the knowledge concerns domain facts, skills and concepts, then the knowledge is traditionally called Bcognitive.^The six ITS that were used as running examples in Behavior of Tutoring Systems were primarily coaching systems for cognitive knowledge. If the knowledge concerns how to do self-regulation, then the knowledge is traditionally called Bmeta-cognitive.^A meta-tutor (e.g., Azevedo and Cromley 2004;Conati and VanLehn 2000;Jackson et al 2010;Roll et al 2011;Zhang et al 2014) is a coaching system for meta-cognitive knowledge. If the knowledge concerns how to collaborate effectively, then the knowledge doesn't have a traditional name, but could be called Bcollaboration skill.^The Soller et al article provides many examples of systems intended to increase collaborative skill.…”
mentioning
confidence: 99%